The Crystal Structure of Mono- and Di-Nuclear Copper(I) Complexes with Substituted Triphenylphosphine Ligands - Costamagna-Martra, J; Costamagna-Martra, J; Lemus-Chavez, L; Lemus-Chavez, L; Arce-Ortega, P; Arce-Ortega, P (Elsevier Ltd, 2015)
Stable mono- and bi-nuclear halide copper(I) complexes with several tri-tolylphosphines as ligands have been synthesized and characterized. Their molecular structures have been determined by X-ray diffraction. Two of these compounds, [CuBr{P(p-tolyl)3}3] and [CuBr{P(m-tolyl)3}3], are distorted tetrahedral mono nuclear species. The binuclear complex [CuCl{P(o-tolyl)3}]2 has the copper atoms linked through μ-chloro bridges in a trigonal planar coordination and they were obtained in two different crystal systems, monoclinic and triclinic. The complex [{(p-tolyl)3P}3Cu2Cl2] is also binuclear but shows two different coordination modes for each copper center: one is a distorted tetrahedral and the other is trigonal planar. In this binuclear complex the 3-coordinate metal is located in an almost planar structure and the Cu2Cl2 moiety lies in a perfect plane. The Cu-P and Cu-X, (X = Cl, Br) distances are dependent on the structural environment. Although the P-Cu-P and P-Cu-X angles depart from the ideal tetrahedral geometry the orthogonal planes containing Cu and two additional atoms are nearly perpendicular. NMR results suggest that bromine compounds retain in solution their structures established in solid. However the chlorine compounds exhibit a dynamic behavior indicating the presence of more than one species in solution. © 2014 Elsevier Ltd. All rights reserved.